Presentation format and reading comprehension: mediation of cognitive and motivational processes - Fuentes Cuiñas, Alejandra (2023)
The aim was to understand the effect of presentation medium (print, digital, and hypertext) on reading comprehension taking into account the mediation of working memory, attentional networks, and self-regulated learning factors. Two SEM models provided good fit to the data showing direct and indirect effects between these variables.